Dangerous liaisons? The role of inflammation and comorbidities in HIV and SARS-CoV-2 infection. (4th March 2021) - Maggi, Paolo; Ricci, Elena; Messina, Vincenzo; Salzillo, Angela; Simeone, Filomena; Iodice, Angelo; Socio, Giuseppe Vittorio
ABSTRACT: Introduction: In people living with HIV (PLWH), immune activation and inflammation levels are high even when viral suppression is maintained, potentially contributing to several comorbidities, and hampering the immune response to infections such as the recent SARS-CoV-2 disease 2019 (COVID-19). Areas covered: Immune activation and inflammation play a role in SARS-CoV-2 infection. Severe COVID-19 patients may experience cytokine release syndrome (CRS), leading to alveolar damage, pulmonary fibrinolysis, dysregulated coagulation, and pulmonary injury. Into the systemic circulation, cytokines in excess might leak out of pulmonary circulation, causing systemic symptoms and possibly a multiple-organ dysfunction syndrome. Preexisting comorbidities are also linked to worse COVID-19 outcome: studies suggest that diabetes and hypertension are linked to higher mortality rates. Such comorbidities are more frequent in PLWH, but it is unclear if they have worse outcomes in the case of COVID-19. The literature was searched in PubMed/MEDLINE and EMBASE, and manually in COVID-19 resources. Expert opinion: A body of evidence shows that HIV and SARS-CoV-2 are able to activate inflammatory pathways, acute in the case of SARS-CoV-2, chronic in the case of HIV, while the comorbidities seem to represent, in the first case, a contributory cause, in the second an effect of the virus-induced damage.